2020
DOI: 10.21203/rs.3.rs-31055/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between neck circumference and the risk of decreased estimated glomerular filtration rate in the general population of China: a cross-sectional study

Abstract: Background: The burden of chronic kidney disease is increasing substantially worldwide. Neck circumference (NC), an anthropometric index for upper-body adiposity, has been recognized as an indicator of cardiometabolic diseases. However, the association between NC and renal dysfunction has not been fully disclosed. The aim of this study was to investigate the association between NC and estimated glomerular filtration rate (eGFR) in the general population in China. Methods: A total of 8805 participants (3322 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Second, since an increased prevalence of obstructive sleep apnea has been observed in women with PCOS (42), xanthine oxidase, an enzyme that plays a key role in uric acid synthesis, could be activated under hypoxic conditions in those patients (43). Third, increasing evidence has shown that more than 60% offree fatty acids (FFAs) are released from upper-body subcutaneous adipose tissue (44). High levels of FFAs exert pathogenic effects on the glomerulus (44) and tubulointerstitium (45), leading to abnormal renal secretion and reabsorption of uric acid (27,46).…”
Section: Discussionmentioning
confidence: 99%
“…Second, since an increased prevalence of obstructive sleep apnea has been observed in women with PCOS (42), xanthine oxidase, an enzyme that plays a key role in uric acid synthesis, could be activated under hypoxic conditions in those patients (43). Third, increasing evidence has shown that more than 60% offree fatty acids (FFAs) are released from upper-body subcutaneous adipose tissue (44). High levels of FFAs exert pathogenic effects on the glomerulus (44) and tubulointerstitium (45), leading to abnormal renal secretion and reabsorption of uric acid (27,46).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, although it has not been included in the diagnostic criteria of metabolic syndrome, is a central factor in the pathogenesis of both MetS and PCOS [33]. In addition, increasing evidence has shown that the variation in NC directly reflects subcutaneous adipose deposition, from which more than 60% of free fatty acids (FFAs) are released [34]. Excessive FFAs have emerged as a major cause of insulin resistance in insulin target organs, which consequently advances the development of MetS [35].…”
Section: Discussionmentioning
confidence: 99%
“…Second, since an increased prevalence of obstructive sleep apnea has been observed in women with PCOS(42), xanthine oxidase, an enzyme that plays a key role in uric acid synthesis, could be activated under hypoxic conditions in those patients (43). Third, increasing evidence has shown that more than 60% of free fatty acids (FFAs) are released from upper-body subcutaneous adipose tissue (44). High levels of FFAs exert pathogenic effects on the glomerulus [42] and tubulointerstitium (45), leading to abnormal renal secretion and reabsorption of uric acid (27,46).…”
Section: Discussionmentioning
confidence: 99%